Fulfillment of Remote Area Elementary School Facilities and Infrastructure Standards - Wiyanto, Wiyanto; Kristiawan, Muhammad; Tahrun, Tahrun (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2022)
In remote areas school experience limitations in fulfilling quality educational facilities and infrastructure. This qualitative research aimed at revealing how schools meet the standard of facilities and infrastructure and what factors influence them. The instruments used were interviews, observation and documentation. The results found that the standard fulfillment of facilities and infrastructure in the Elementary Schools Public 25 at Muara Sugihan District was still low compared from several other public elementary schools at the Muara Sugihan sub-district. The Principal explained that the factors influence it include geographical location, the role of community leaders, parents of students, educators and. Facilities for the provision of necessities related to facilities should be carried out jointly by all school members.